Stolen prey - Sandford, John, 1944 Feb. 23- (New York : G.P. Putnam's Sons, 2012)
In the small Minnesota town, an entire family has been killed. To Lucas Davenport it looks like retribution he's seen in drug killings. It just doesn't seem to fit; until it does. And where it leads Lucas will take him into the darkest nightmare of his life
Keywords: Davenport, Lucas (Fictitious character) -- Fiction; Private investigators -- Minnesota -- Minneapolis -- Fiction; Families -- Crimes against -- Fiction; Mystery fiction